Time to exhaustion at traditional physiological indicators in runners: Between-subject and between-day variability - Pallarés, J. G.; Valenzuela, P. L.; Martínez-Cava, A.; Higuera-Liébana, E.; Buendía-Romero, Á.; Cervantes, A.; Mora-Rodriguez, R. (International Journal of Sports Physiology and Performance, 2026)
Background: The maximum oxygen uptake (VO2max), respiratory compensation point (RCP), and maximal lactate steady state (MLSS) are indicators used to assess athletes` performance. There is scarce information available on the tolerable duration of exercise (time to exhaustion [TTE]) while running at these physiological indicators. We aimed to analyze the TTE when running at these indicators, as well as to determine their between-subject variability and within-subject reliability.